Leaf–air temperature difference as a reliable indicator for potato water status - Liu, Peng; Guan, Ting; Fan, Mingshou; Guo, Jiawei; Wang, Meirong; Shang, Zhihui; Jia, Liguo (Frontiers in Plant Science, 2025)
IntroductionPotato (Solanum tuberosum L.) production in semi-arid regions requires precision irrigation management to address water scarcity, highlighting the critical need for real-time, non-destructive plant water status assessment techniques. This study aimed to investigate the feasibility of measuring the leaf–air temperature difference (LAD) as an indicator for diagnosing potato water status.MethodsA field experiment was conducted with five irrigation levels (0–300 mm) to evaluate LAD responses at three leaf positions (L1, L4, and L8) across different growth stages.ResultsThe results demonstrated that LAD significantly correlated with irrigation levels, plant water content (PWC), and soil moisture, with the strongest relationships observed for the fourth leaf from the top (L4). L4 exhibited the highest sensitivity to water status, the lowest variability among plants. A binomial regression between LAD and yield was identified, revealing a threshold LAD beyond which further LAD increases did not enhance the yield. These findings not only suggest that LAD can be a reliable indicator for monitoring potato water status but also identify L4 as the optimal leaf position for LAD-based water status monitoring.DiscussionThe study provides a foundation for precision irrigation in potato production, enabling improved water use efficiency and sustainable potato production in a semiarid region.